2005
DOI: 10.1093/humrep/deh672
|View full text |Cite
|
Sign up to set email alerts
|

Two cycles with single embryo transfer versus one cycle with double embryo transfer: a randomized controlled trial

Abstract: Two cycles with SET were equally effective as one cycle with DET, and the medical costs per live birth up to 6 weeks after delivery were the same. However, if lifetime costs for severe handicaps are included, more than 7000 per live birth will be saved after implementing SET. Because of the high probability of multiple pregnancies in this group of IVF patients, only SET should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 28 publications
7
146
1
2
Order By: Relevance
“…Moreover, elective single embryo transfer with an acceptable pregnancy rate might be considered if a top quality embryo is available. The pregnancy rate of oncetransfer was 40%, and the cumulative pregnancy rate was 60%, equal to even higher than the cumulative pregnancy rate of double-embryo transfer [41][42][43]. The quality of embryos (cleavage speed and morphologic distribution): embryos that absence of multinucleated blastomeres, four or five blastomeres on day 2, seven or more cells on day 3, and ≤20% anucleated fragments are considered as top quality embryos [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elective single embryo transfer with an acceptable pregnancy rate might be considered if a top quality embryo is available. The pregnancy rate of oncetransfer was 40%, and the cumulative pregnancy rate was 60%, equal to even higher than the cumulative pregnancy rate of double-embryo transfer [41][42][43]. The quality of embryos (cleavage speed and morphologic distribution): embryos that absence of multinucleated blastomeres, four or five blastomeres on day 2, seven or more cells on day 3, and ≤20% anucleated fragments are considered as top quality embryos [44].…”
Section: Discussionmentioning
confidence: 99%
“…However it has been reported that, even though eSET elevates the chance of delivering a healthy baby compared to double embryo transfer (DET) in cleavage stage embryo [7], eSET results in significantly decreased pregnancy and delivery rates per embryo transfer [8,9]. In contrast to these results, it has been reported that the clinical outcomes of elective single blastocyst embryo transfer (eSBET) are similar to those of double blastocyst embryo transfer (DBET) on day 5 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Randomised studies [7,14,[20][21][22] comparing 1 or 2 embryo transfer on a population at risk of multiple pregnancies (maternal age <36 or 34 years, number of high quality embryos) shows a decrease of pregnancy rate in fresh cycles. Therefore thawing frozen embryos allows the re-establishing of pregnancy rate which was otherwise decreased.…”
Section: Discussionmentioning
confidence: 99%